A Flaw in the Movement - Scopetea, Sophia (KIERKEGAARDIANA, 1984)
A Flaw in the Movement: Pondering on Some Extensive Footnotes in The Concept of Anxiety with Temporary Remarks on Kierkegaard’s Usage of Greek